2016
DOI: 10.1080/17441692.2015.1134613
|View full text |Cite
|
Sign up to set email alerts
|

A global research synthesis of HIV and STI biobehavioural risks in female-to-male transgender adults

Abstract: There is a growing interest in HIV infection and sexually transmitted infection (STI) disease burden and risk among transgender people globally; however, the majority of work has been conducted with male-to-female (MTF) transgender populations. This research synthesis comprehensively reviews HIV and STI research in female-to-male (FTM) transgender adults. A paucity of research exists about HIV and STIs in FTMs. Only 25 peer-reviewed papers (18 quantitative, 7 qualitative) and 11 ‘grey literature’ reports were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 44 publications
(40 reference statements)
2
66
0
Order By: Relevance
“…In a recent review, estimates of recent condomless vaginal or anal intercourse ranged from 7–69% [18]. The inclusion in many studies of transgender men regardless of the sex of their partners contributes to this variability, as most of their sexual partners are cisgender women [19].…”
Section: Hiv Vulnerabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, estimates of recent condomless vaginal or anal intercourse ranged from 7–69% [18]. The inclusion in many studies of transgender men regardless of the sex of their partners contributes to this variability, as most of their sexual partners are cisgender women [19].…”
Section: Hiv Vulnerabilitiesmentioning
confidence: 99%
“…Condomless vaginal intercourse appears more frequent than condomless anal intercourse among transgender men [19, 22]. While this may contribute to lower HIV risk, transgender men using testosterone therapy may experience vaginal tissue changes (similar to menopausal cisgender women [23]) that may increase susceptibility to HIV infection [18]. …”
Section: Hiv Vulnerabilitiesmentioning
confidence: 99%
“…Although HIV prevalence in TMSM ranges from 0 to 3% in the small convenience sample studies conducted to date, 1,3-5,11-13 self-reported lifetime STI histories range from 6% to 47%, 3 and current HIV-related sexual risk behaviours from 7% to 69% depending on how risk was operationalised. 3-5 A national study of TMSM ( n = 45) found that only 31% reported “always” using a condom during vaginal sex, 40% reported using a condom “always” during anal sex, and 91% had a previous STI diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…5–7 In the United States, HIV research on transgender men (assigned a female sex at birth) is eclipsed by that on transgender women (assigned a male sex at birth), mainly because estimates of HIV prevalence are higher (25%–31%) among transgender women than among transgender men (0%–3%). 6 However, research suggests that transgender men who have sex with men are at increased risk for HIV acquisition, 8,9 and transgender men constitute 15.4% of the newly diagnosed HIV cases among trans-gender persons. 10 Transgender men are an understudied population lacking evidence-based HIV interventions to address their needs.…”
mentioning
confidence: 99%
“…Surveillance systems designed to monitor health outcomes of the general population often lack adequate data about gender identity, making it difficult to distinguish between transgender and cisgender persons. 9 This article is the first to present sociodemographic, clinical, and behavioral characteristics of HIV-positive transgender men drawn from a representative sample of adults receiving medical care in the United States.…”
mentioning
confidence: 99%